Experimental study on the crashworthiness of bio-inspired aluminum foam-filled tubes under axial compression loading. (October 2020) - Song, Jiafeng; Xu, Shucai; Xu, Lihan; Zhou, Jianfei; Zou, Meng
Abstract: As a lightweight and efficient energy-absorbing structure, thin-walled filled structure is widely used in various fields. This paper proposed four types of bio-inspired foam-filled thin-walled structures based on two typical straw structures (Cornstalk and Reed): bionic foam core with a central hole, 4 square holes, 4 taper holes and 2 nodes, respectively. The energy absorption capacity and deformation mode of bionic structures were studied by dynamic drop hammer and quasi-static compression. The results showed that 9 of 12 bionic samples had higher energy absorption capacity than the corresponding fully-filled samples. Different bionic features have different effects on the deformation of thin-walled tube, and the bionic features with the best overall performance are the 4 Square Holes and 4 Taper Holes design. It is noted that the bionic method can improve energy absorption capacity and affect the deformation mode of the thin-walled tubes under certain conditions. Highlights: Serious of bionic foam-filled energy absorption tubes were designed inspired by the structure of cornstalk and reed straw. Drop weight and quasi-static compression experiments were conducted to study the energy absorption capacity of those tubes. Deformation and energy absorption mechanism during the experiment were analyzed. Influence of bionic features on the energy absorption tube was analyzed.